2015
DOI: 10.1007/s11356-015-4746-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of transpiration in arsenic accumulation of hyperaccumulator Pteris vittata L.

Abstract: A b s t r a c t M e c h a n i s m s o f P t e r i s v i t t a t a L . t o hyperaccumulate arsenic (As), especially the efficient translocation of As from rhizoids to fronds, are not clear yet. The present study aims to investigate the role of transpiration in the accumulation of As from the aspects of transpiration regulation and ecotypic difference. Results showed that As accumulation of P. vittata increased proportionally with an increase in the As exposure concentration. Lowering the transpiration rate by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…It should be noted that plant transpiration is limited for plant culture in agar media, while the role of transpiration in hyperaccumulation has been demonstrated (e.g. for arsenic accumulation in Pteris vittata L. (ladder brake)). Hence, confirmation of the hyperaccumulation status of the plants studied in the present work in field trials may still be of value.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that plant transpiration is limited for plant culture in agar media, while the role of transpiration in hyperaccumulation has been demonstrated (e.g. for arsenic accumulation in Pteris vittata L. (ladder brake)). Hence, confirmation of the hyperaccumulation status of the plants studied in the present work in field trials may still be of value.…”
Section: Resultsmentioning
confidence: 99%
“…SbIII and AsIII are both neutral solutes, and thus passive diffusion or other transporters may participate in the efficient uptake of AsIII and SbIII in P. vittata. An earlier study indicated that the transpiration of P. vittata greatly contributed to the uptake of AsIII (Wan et al 2015a), thereby implying the role of passive diffusion in As accumulation and its possible role in SbIII accumulation.…”
Section: Discussionmentioning
confidence: 98%
“…An important role of transpiration in As translocation from root-to-shoot has been revealed in P. vittata. It was observed by Wan et al (2015) that subjecting the plants to shade to reduce transpiration by 28–67% decreased shoot As by 19–56%. They further compared ecotypes of P. vittata from moister and warmer habitat having high transpiration rate with ecotypes from drier and cooler habitat and found that ecotypes with higher transpiration also had higher As in shoot.…”
Section: Transporters For Uptake and Translocation Of Arsenicmentioning
confidence: 99%